Observation of coherent Smith-Purcell and transition radiation driven by single bunch and micro-bunched electron beams - Liang, Y; Du, Y; Su, X; Wang, D; Yan, L; Tian, Q; Zhou, Z; Wang, D; Huang, W; Gai, W; Tang, C; Konoplev, I; et al. (American Institute of Physics, 2018)
Generation of coherent Smith-Purcell (cSPr) and transition/diffraction radiation using a single bunch or a pre-modulated relativistic electron beam is one of the growing research areas aiming at the development of radiation sources and beam diagnostics for accelerators. We report the results of comparative experimental studies of terahertz radiation generation by an electron bunch and micro-bunched electron beams and the spectral properties of the coherent transition and SP radiation. The properties of cSPr spectra are investigated and discussed, and excitations of the fundamental and second harmonics of cSPr and their dependence on the beam-grating separation are shown. The experimental and theoretical results are compared, and good agreement is demonstrated.